GEOGRAPHICAL NAMES IN THE WORLD - Raper, Peter E. (Scientia Militaria - South African Journal of Military Studies, 2012)
(ADDRESS DELIVERED AT FIRST MILITARY NAMES CONGRESS HELD AT FORT KLAPPERKOP ON 30 OCTOBER 1992) A geographical name, sometimes also called a place name or toponym, is the name of any portion of the Earth that has a recognizable identity. Toponyms include the names of all natural and man-made features on and under the surface of the earth. Since the time when people first started to communicate among themselves, the names they gave to features have played a very important role in their vocabulary. In recent times the use of geographical names has increased greatly because of the sophisticated communication technology and the great progress made in the media and printing.